A case for a quantum informed approach to health communication research - Parrish-Sprowl, John; Parrish-Sprowl, Susan (Frontiers in Communication, 2023)
Foundational social science has dominated health communication research, especially in the mainstream of Western scholarship. Alternative ways of conceptualizing, including most if not all indigenous ways of thinking, have often been relegated to second class status, if regarded at all. For those who questioned prevailing wisdom in the past, the choice regarding theory and research seemed to be one of going in a more interpretive or critical direction and leaving ‘science’ behind or staying within a framework they found wanting in many ways. Ironically, the work of such Communication scholars as Pearce, Dutta, and others, often born from interpretative and critical perspectives, is much more consonant with quantum framed science than social science as practiced. Indeed, much of the body of indigenous perspectives align with quantum theory informed science better than social science as practiced. As we move through the 21st century, it is time that communication theory and research, especially in health communication, moves to reclaim science in ways that shift us from a Newtonian understanding of the world to more a quantum paradigm. As we do so, we will likely find that many who have been on the margins can and should move their work to the mainstream, albeit with a process that synthesizes their work with quantum science. This would help us move forward in ways that not only invite more inclusion, but also create more meaningful ways of conceptualizing communication and its relationship to health.